2019
DOI: 10.26452/ijrps.v10i4.1745
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anti bacteria effects of citrate-reduced silver nanoparticles in Staphylococcus aureus and Escherichia coli

Abstract: Silver nanoparticles (AgNPs) has long known for its inhibitory and bactericidal effects. However, due to its’ attractive antibacterial property, on-going research with various synthesis strategies actively been conducted. In this study, the synthesis of AgNPs was reported, using a simple chemical reduction method with citrate as the reducing agent TEM was used to characterize the obtained AgNPs. Then, Staphylococcus aureus and Escherichia coli were used to identify the antibacterial activity of AgNPs. The inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
2
1
0
Order By: Relevance
“…Our results clearly show an antibacterial activity (even low) of AuNPs against E. coli ATCC 25922 and S. aureus ATCC 25923, which strongly differs from recent studies that failed to report any significant antibacterial activity of AuNPs against the same bacterial strains [37,38]. A contrario, for AgNPs, our results seem to be consistent with other studies which found that citrate-capped silver NPs showed a higher activity against E. coli than S. aureus [39][40][41][42]. For example, minimal bactericidal concentrations (MBC) of 9.94 µg/mL (i.e., ≈92 µM of metal) and 19.88 µg/mL (i.e., ≈184 µM) were obtained by C. Quintero-Quiroz et al, for AgNPs (5-50 nm) against E. coli ATCC 25922 and S. aureus ATCC 29213, respectively [40].…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Our results clearly show an antibacterial activity (even low) of AuNPs against E. coli ATCC 25922 and S. aureus ATCC 25923, which strongly differs from recent studies that failed to report any significant antibacterial activity of AuNPs against the same bacterial strains [37,38]. A contrario, for AgNPs, our results seem to be consistent with other studies which found that citrate-capped silver NPs showed a higher activity against E. coli than S. aureus [39][40][41][42]. For example, minimal bactericidal concentrations (MBC) of 9.94 µg/mL (i.e., ≈92 µM of metal) and 19.88 µg/mL (i.e., ≈184 µM) were obtained by C. Quintero-Quiroz et al, for AgNPs (5-50 nm) against E. coli ATCC 25922 and S. aureus ATCC 29213, respectively [40].…”
Section: Discussionsupporting
confidence: 59%
“…However, with AgNPs of 95.5 nm in diameter (large size distribution) facing the same strains, M. Zarei et al, reported no antibacterial activity against E. coli, while they determined a MIC of 5 µg/mL (i.e., ≈46 µM of metal) against S. aureus [43]. Moreover, 12.9 ± 4.5 nm AgNPs, prepared from silver nitrate, sodium citrate and ascorbic acid, tested against E. coli (MG 1655) and S. aureus (ATCC 6538) led to the determination of MBC of 0.14 mg/mL (i.e., 1.3 µM) and 0.35 mg/mL (3.2 µM) respectively [41]; whereas AgNPs ranging from 1 to 20 nm facing E. coli (ATCC 25922) and S. aureus (ATCC 12600) resulted in MIC of 0.049 mg/mL (i.e., ≈454 µM) and 0.391 mg/mL (i.e., 3625 µM) [42]. The differences observed with our results can be attributed to the AgNPs large size distribution [40,43], the presence of an antibacterial agent in the NPs preparation procedure [41], or the selection of different bacteria strains and concentration range (more specifically when S. aureus is under consideration) [41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Similar conditions were observed in our previous study [45]. The Gram-negative P. aeruginosa cell wall is composed of lipopolysaccharides (LPS) with a highly negative charge that promotes the adhesion of AgNPs [46]. In addition, internalization of bioAgNPs into Gram-negative bacteria is seen as effective due to the different membrane structure.…”
Section: Tested Bacteriasupporting
confidence: 82%